A transferência irônica como forma de relação com o Outro na esquizofrenia - Carrilho, Marina Moreira (2021)
Considering that the psychoanalytic literature on psychoses proposed by Lacan is almost entirely focused on the paranoia paradigm, we ask ourselves which language indices is more accurate to identify and differentiate paranoia from schizophrenia as a personality structure. To develop this work, we had as a starting point the lacanian statement in the text “Responses to students of philosophy” (1966), in which irony is said to be a form of schizophrenic defense against the social bond. Along with this, we get closer to the concept of ironic transference conceived by Alomo (2012), which refers to an specific type of relationship between a subject and the Other of language. It was observed that this relationship is similar to some linguistic attempts to apprehend the ironic phenomenon and to the conceptualization of irony as defined by Kierkegaard, thus revealing a relationship of knowledge that satirize the inconsistency of the Other as guarantor of the truth